Pluralité et territoires dans les espaces publics au Chili : Réflexions sur une action collective située - Emmanuelle Barozet (Centre de Recherches sur les Mondes Américains, 2012)
This article examines how civil middle-class associations have emerged in the last two decades, in order to defend specific neighborhoods in Santiago de Chile, from a theoretical point of view and also using fieldwork observations. Through this situated collective action, the inhabitants redefine their local spaces and configure different categories concerning themselves such as citizenship and social participation. Citizens carry these controversies about public spaces in different arenas, introducing in the debates notions such as neighborhood and environment.